Speaking with Native Speakers to Improve Speaking Skills - Pranata, Heri; Al Farisi, Khaerul Wathoni; Iddiyaturrohmah, Mahyam; Wardana, Ali; Jaelani, Selamet Riadi (STAI Denpasar Bali, 2023)
Speaking is one of the four macro skills to be developed as a means of effective communication in both first and second language learning contexts. In the English as a Foreign Language (EFL) pedagogy environment, improving speaking competence and confidence for the undergraduate students tends to be a major challenge faced by students. This study examines the effect of undergoing speaking with native speakers to improve students speaking competency. A descriptive qualitative method has been employed to explore the impact of speaking with native speakers to improve students speaking competence. Initially, the participants of this study came from the fourth, sixth and second semester of English Study Program of Sunan Doe Institute in the academic year of 2020 – 2023 which comprised 80 students. The result of the study revealed that talking with native speakers is a very effective method to improve speaking skills especially for the sixth, fourth and second semester of English students of Sunan Doe Institute who had undergone practice of speaking with native speakers. A more detailed findings were discussed further.